HUBUNGAN KECERDASAN EMOSIONAL DENGAN KINERJA PERAWAT DALAM MENERAPKAN ASUHAN KEPERAWATAN DI IRINA A RSUP PROF. DR. R. D. KANDOU MANADO - Paomey, Christian Jake; Mulyadi, Ns; Hamel, Rivelino (JURNAL KEPERAWATAN, 2016)
Abstract:. Low emotional intelligence is one of the weaknesses of human resources in developing countries. Emotional intelligence refers to an array of non-cognitive skills that influence person’s ability. Emotional intelligence is a factor that can influence nurse’s performance in applying nursing care. Aim of the study: is to identify the relationship between emotional intelligence and nurse’s performance in applying nursing care. Methods: design of this study using analytic survey with cross sectional approach. The population are all nurses who work at inpatient department A in Prof. Dr. D. R. Kandou Manado Hospital and using total sampling technique that involved 37 nurses. The tools were used in this study are nurses emotional intelligence questionnaire sheet and nurse’s performance in applying nursing care checklist observation sheet. Result: analysis was using Fisher's Exact Test with a significance level of 95% (ɑ = 0,05) and shows that the p value is 0.006. Conclusion: there is a relationship between emotional intelligence and nurse’s performance in applying nursing care at Inpatient Department A in Prof. Dr. D. R. Kandou Manado Hospital. Recommendations: Emotional intelligence training programs can be held for nurses to increase emotional intelligence. Emotional intelligence can be considered as a factor in nurses selection. Educational preparation for nurse students can be held  by incorporating lessons or materials related to emotional intelligence in nursing curriculum. Further research is needed to explore how much emotional intelligence affect nurse’s performance and explore the component of emotional intelligence which is most influence nurse’s performance in applying nursing care. Keywords : emotional intelligence, nurse’s performance, nursing care. Abstrak: Kecerdasan emosional yang rendah merupakan salah satu kelemahan sumber daya manusia di negara berkembang. Kecerdasan emosional merujuk ke kumpulan keterampilan nonkognitif yang mempengaruhi kemampuan seseorang. Kecerdasan emosional merupakan faktor yang dapat mempengaruhi kinerja perawat dalam menerapkan asuhan keperawatan.Tujuan Penelitian: mengetahui hubungan kecerdasan emosional dengan kinerja perawat dalam menerapkan asuhan keperawatan. Metode: menggunakan desain penelitian survey analitik dengan pendekatan cross sectional. Populasi adalah seluruh perawat di Irina A RSUP Prof. Dr. D. R. Kandou Manado. Teknik pengambilan sampel menggunakan total sampling dengan jumlah 37 sampel. Pengumpulan data menggunakan kuesioner dan lembar observasi. Hasil: analisis menggunakan Fisher's Exact Test dengan tingkat kemaknaan 95% (α=0.05) dan menunjukan nilai p=0.006. Simpulan: terdapat hubungan antara kecerdasan emosional dengan kinerja perawat dalam menerapkan asuhan keperawatan di Irina A RSUP Prof. Dr. D. R. Kandou Manado. Saran: program pelatihan kecerdasan emosional dapat diberikan bagi perawat untuk mengembangkan kecerdasan emosional. Kecerdasan emosional dapat dipertimbangkan sebagai faktor dalam seleksi perawat. Pelajaran yang berkaitan dengan kecerdasan emosional dapat ditambahkan pada kurikulum pendidikan keperawatan. Penelitan lanjut yang dapat melihat besar pengaruh kecerdasan emosional tehadap kinerja perawat dan menjunjukan wilayah kecerdasan emosional mana yang paling berhubungan/mempengaruhi kinerja perawat dalam menerapkan asuhan keperawatan. Kata Kunci : kecerdasan emosional, kinerja perawat, asuhan keperawatan